Biblical women in contemporary novels in English - Bertrand, Ingrid (Costerus, 2020)
How are well-known female characters from the Bible represented in late 20th-century novels? In Biblical Women in Contemporary Novels in English, Ingrid Bertrand presents a detailed analysis of biblical rewritings by Roberts, Atwood, Tennant, Diamant and Diski focusing on six different women (Eve, Noah's wife, Sarah, Bilhah, Dinah and Mary Magdalene). She shows how these heroines give themselves a voice that rests not only on words but also on silences. Exploring the many forms that silence can take, she presents an innovative typology that sheds new light on this profoundly meaningful phenomenon.